Disaster-causing mechanism and prevention and control vision orientation of different types of coal seam floor water disasters in China - Yifan ZENG; Huicong ZHU; Qiang WU; Houzhu WANG; Xianjie FU; Tieji WANG; Xirui WANG; Jiulin FAN; Rongjie HU; Xiangjun CAI; Xuedong KAN; Shengbao GAO (Meitan xuebao)
China’s coal-forming conditions are harsh, the coal-bearing environment is complex and changeable, and the resources are distributed in a global, multi-geological type and scattered distribution, resulting in frequent occurrence of mining-associated geological disasters. At the same time, with the optimization and regulation of coal resource development layout, the negative orientation of coal seam floor water damage is becoming more and more significant. The synergistic effect of high confined water hydraulic drive and strong sensitive defect structure activation leads to a significant increase in the threat of macroscopic dynamic representation of coal seam floor water damage, which has become an endogenous resistance to the high-quality transformation and development of coal resources in China. In order to grasp the development situation of coal seam floor water disaster in China in an all-round way and discuss the key research direction of prevention and control operation based on new technology in the future, the dynamic evolution trend of coal seam floor water disaster in China in recent years is comprehensively demonstrated from the multi-dimensional perspectives of time, space and water inrush quantity. The type is divided into “total-sub” type, and the mechanical mutual feedback response mechanism of coal seam floor water disaster in China is discussed by establishing geomechanical model. Based on the macroscopic representation of disaster, the endogenous disaster-causing mechanism is revealed, and the new development path and vision orientation of prevention and control technology concept are pointed out. The results show that: The evolution law and characteristics of coal seam floor water disasters in China from a multi-dimensional perspective are statistically analyzed, and the main framework of coal seam floor water disasters in China is discussed and established. According to the accident core cause system and macroscopic disaster-causing representation, the coal seam floor water disasters are divided into three categories: karst collapse column water inrush, fault activation water inrush and fracture-induced (composite) limestone water inrush, which are further refined into 12 subcategories, such as full-path through incremental water inrush (karst collapse column), through coal seam water inrush (fault), single-layer direct water inrush (fracture) with mining and unloading. The geographical spatial distribution of water disasters in three major types of coal seam floors was analyzed independently. The mechanism of ground stress and confined water pressure on the alienation development of confined water conduction path in the process of water inrush from karst collapse column is analyzed. The water inrush mode of floor karst collapse column induced by dynamic/static load disturbance of overburden roof is proposed, and its mechanical starting conditions and disaster-causing mechanism are clarified. The generalized model of macro-micro geomechanical structure of coal seam floor fault is established. Based on the identification of the core disaster-causing factors that induce fault activation water inrush, the mechanical criteria of fault activation water inrush in different types of coal seam floor are established. Based on the fracture as the basic unit, the critical discriminant conditions for the inrush of fissure-type ascending (composite) limestone water induced by single-layer and composite-layer confined aquifers are established by the formula of “one to n”, and the disaster-causing mechanism of the whole process of this type of floor water disaster is revealed. On the basis of summarizing the current concept of coal seam floor water disaster detection, prediction and control technology, combined with the frontier development direction, it is pointed out and suggested that the three-dimensional dynamic reconstruction of the whole life cycle mining-induced mutation characteristics of the background geological gene of the coal seam floor, the upgrading of the concept of coal seam floor water inrush prediction and prediction suitable for the dynamic geological environment of space-time differentiation, the application of low disturbance and strong intervention with mining\water control and mutual grouting treatment technology, and the establishment of long-term monitoring, diagnosis and treatment platform for geological ecosystem after restoration should be carried out to build a large system of full-time and space-time prevention and control of coal seam floor water disaster, and keep up with the development of new formats in the whole coal industry under the background of new productivity.